1987
DOI: 10.1161/01.cir.75.5.1058
|View full text |Cite
|
Sign up to set email alerts
|

The preventive effect of verapamil on ethanol-induced cardiac depression: phosphorus-31 nuclear magnetic resonance and high-pressure liquid chromatographic studies of hamsters.

Abstract: Alcoholic depression of left ventricular function was produced in normal hamsters by the administration of increasing concentrations of alcohol in drinking water (up to 50%) for 6 months. The result was assessed by phosphorus-3 1 nuclear magnetic resonance of isolated perfused hearts and high-pressure liquid chromatography of freeze-clamped tissues. Hemodynamic data and myocardial oxygen consumption were also monitored. Alcoholic hamsters had significantly higher inorganic phosphate and lower ATP levels, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 29 publications
2
10
1
Order By: Relevance
“…Chronic alcohol exposure in the hamster was previously shown to cause both depression of left Ventricular function and associated alterations in high-energy phosphate metabolism (10). In contradistinction, the current study involving acute alcohol exposure of the isolated rat heart found depression of cardiac function but no change in myocardial energy.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Chronic alcohol exposure in the hamster was previously shown to cause both depression of left Ventricular function and associated alterations in high-energy phosphate metabolism (10). In contradistinction, the current study involving acute alcohol exposure of the isolated rat heart found depression of cardiac function but no change in myocardial energy.…”
Section: Discussioncontrasting
confidence: 63%
“…The influence of chronic alcohol treatment was studied earlier (10). Prolonged ingestion of alcohol caused a decrease in high-energy metabolites along with depressed cardiac performance (10). In these earlier studies, however, the hearts were removed from the animal and perfused in an alcohol-free medium, and thus we were assessing not only the direct chronic influence of alcohol on the heart but also the influence of alcohol withdrawal.…”
mentioning
confidence: 99%
“…Alcohol consumption has been long-recognized as one of the major risk factor for developing dilated cardiomyopathy (166). Alcohol has been shown to have the many negative effects on myocardial function: myocytolysis and fibrosis (167), impaired sarcoplasmic reticular uptake of calcium (168), inhibition of myosin ATPase (169), reduction in myocardial high-energy phosphates (170) and impairment in diastolic function (171). Although heavy intake of alcohol that is regular and of prolonged duration is associated with dilated cardiomyopathy, light to moderate alcohol intake may actually protect the heart from developing heart failure (172).…”
Section: Alcohol-induced Cardiomyopathy Recommendationmentioning
confidence: 99%
“…Alcohol causes membrane changes, including impaired Na+K+ ATPase activity and inhibition of NafCa2+ exchange (5). Chronic intake of high doses of ethanol causes impairment of mitochondrial function and diminished phosphate-to-oxygen ratios (6)(7)(8)(9). Highenergy phosphate levels are depressed in alcoholic cardiomyopathy (6,7).…”
mentioning
confidence: 99%
“…Chronic intake of high doses of ethanol causes impairment of mitochondrial function and diminished phosphate-to-oxygen ratios (6)(7)(8)(9). Highenergy phosphate levels are depressed in alcoholic cardiomyopathy (6,7). Abnormal-ities in mitochondria1 function as a response to ethanol (8, 9) may be due to the formation of free fatty acid ethyl esters, which bind to mitochondria and are subsequently hydrolyzed, releasing free fatty acids (10,11).…”
mentioning
confidence: 99%